2019
DOI: 10.1088/2058-6272/ab4722
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of constricted and diffusive arc–anode attachments in wall-stabilized transferred argon arcs

Abstract: A numerical simulation is conducted to investigate arc-anode attachment behavior, especially the formation mechanism of the constricted arc attachment mode for the water-cooled anode of wall-stabilized transferred argon arcs. Argon molecular ions and the corresponding kinetic processes are included to the finite-rate chemistry model in order to capture the chemical nonequilibrium characteristics of the arc near the anode region. Modeling results show that constricted and diffusive arc-anode attachments can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…The temperature gradients of experimental data are steep, while the gradients at the same position are underestimated by the numerical model. The predicted results of the same numerical approach are also compared with the experimental results presented in [65], as shown in [40]. Generally, the results of numerical simulation predictions are acceptable in this simulation.…”
Section: Comparison and Verification Of Numerical Simulation Results ...mentioning
confidence: 81%
See 1 more Smart Citation
“…The temperature gradients of experimental data are steep, while the gradients at the same position are underestimated by the numerical model. The predicted results of the same numerical approach are also compared with the experimental results presented in [65], as shown in [40]. Generally, the results of numerical simulation predictions are acceptable in this simulation.…”
Section: Comparison and Verification Of Numerical Simulation Results ...mentioning
confidence: 81%
“…S c,s is the chemical reaction source term which is determined by different kinetic processes shown in table 1. The diffusion flux  J s are obtained from equation (2) [40,41]. Here, p is the gas pressure.…”
Section: Main Assumptions and Governing Equationsmentioning
confidence: 99%
“…The plasma discharge equations, which are almost the same as in our previous papers [36][37][38], describe the species densities, electron and heavy-species temperature, the electric field, selfinduced magnetic field and velocity field in the wall-stabilized transferred arc. The governing equations used for the 3D transferred arc plasma are presented below.…”
Section: System Of Equationsmentioning
confidence: 98%
“…Previous numerous experimental studies and numerical simulations have shown that the arc may attach to the anode in a diffuse or constricted mode [8][9][10][11]. If the arc-forming gas is a molecular gas, such as the widely used nitrogen, the arc is usually attached to the anode in a constricted mode.…”
Section: Introductionmentioning
confidence: 99%